Expression of TaNCL2-A ameliorates cadmium toxicity by increasing calcium and enzymatic antioxidants activities in arabidopsis. (July 2023) - Shumayla; Tyagi, Shivi; Sharma, Yashraaj; Madhu; Sharma, Alok; Pandey, Ashutosh; Singh, Kashmir; Upadhyay, Santosh Kumar
Abstract: Cadmium (Cd) is a heavy metal that occurs naturally in the environment and is toxic to both animals and plants. The impact of Cd toxicity is shown to be reduced by the exogenous application of calcium (Ca) in crop plants. The sodium/calcium exchanger-like (NCL) protein is involved in Ca enrichment in the cytoplasm by transporting it from the vacuole in the exchange of cytosolic sodium (Na). However, it has not been utilized to ameliorate the Cd toxicity, to date. An elevated expression of TaNCL2-A gene in the root and shoot tissues of bread wheat seedlings, and a higher growth rate of recombinant yeast cells, suggested its role in Cd stress response. The TaNCL2-A expressing transgenic Arabidopsis lines exhibited significant Cd tolerance with increased Ca (∼10-fold) accumulation. The proline content and antioxidant enzymes activities were increased while oxidative stress-related molecules such as H2 O2 and MDA were reduced in the transgenic lines. In addition, the growth and yield parameters of transgenic lines such as seed germination rate, root length, leaf biomass, leaf area index, rosette diameter, leaf length and width, and silique count, along with various physiological indicators like chlorophyll, carotenoid, and relative water contents were also improved in comparison to the control plants. Further, the transgenic lines exhibited significant salinity and osmotic stress tolerance, as well. Taken together, these results suggested that the TaNCL2-A could mitigate Cd toxicity along with salinity and osmotic stress. This gene may also be utilized for phytoremediation and Cd sequestration in future studies. Graphical abstract: Image 1 Highlights: TaNCL2-A showed induced expression after Cd treatment in wheat seedlings. Recombinant yeast cells expressing TaNCL2-A exhibited an increased growth rate under different concentrations of Cd. TaNCL2-A expression mitigate Cd toxicity in transgenic lines with improved morpho-physiological and biochemical processes. Transgenic Arabidopsis lines also displayed salinity and osmotic stress tolerance.